Apoptosis-targeted gene therapy for non-small cell lung cancer using chitosan-poly-lactic-co-glycolic acid -based nano-delivery system and CASP8 and miRs 29A-B1 and 34A - Chattopadhyay, Sourav; Sarkar, Shashanka Shekhar; Saproo, Sheetanshu; Yadav, Sheetal; Antil, Deepika; Das, Bodhisatwa; Naidu, Srivatsava (Frontiers in Bioengineering and Biotechnology, 2023)
Non-small cell lung cancer (NSCLC) is a leading cause of cancer-related deaths worldwide, with resistance to apoptosis being a major driver of therapeutic resistance and aggressive phenotype. This study aimed to develop a novel gene therapy approach for NSCLC by targeting resistance to apoptosis. Loss of function mutations of caspase 8 (CASP8) and downregulation of microRNAs (miRs) 29A-B1 and 34A were identified as key contributors to resistance to apoptosis in NSCLC. A biodegradable polymeric nano-gene delivery system composed of poly-lactic-co-glycolic acid (PLGA) was formulated to deliver initiator CASP8 and miRs 29A-B1 and 34A. The nano-formulation efficiently encapsulated the therapeutic genes effectively internalized into NSCLC cells and induced significant apoptosis. Evaluation of the nano-formulation in A549 tumor spheroids showed a significant increase in apoptosis within the core of the spheroids, suggesting effective penetration into the spheroid structures. We provide a novel nano-formulation that demonstrate therapeutic potential for suicidal gene therapy in NSCLC.